(untitled) (Journal of Guidance and Counselling Studies, 2023)
Descriptive research design was employed to investigate the psychological dimensions and measures for curbing bullying among in-school adolescents in Anambra state-Nigeria. Two research questions and two hypotheses tested at 0.05 level of significance guided the study.The population comprised all the 5, 827 teachers and 261 principals from the 261 secondary schools in Anambra state. A sample of 450 teachers and 90 principals was randomly selected from the 6 education zones using simple random sampling procedure. A researcher-developed questionnaire named “Psychological Dimensions of Bullying” (PDB) was used for data collection. The instrument was validated by three specialists in Education. The reliability of the instrument was determined using Cronbach alpha method and alpha coefficient of 0.79 was obtained. The research questions were answered using mean and standard deviation while t-test was employed for testing the hypotheses. The result of the study revealed that 17 psychological factors were identified by principals and teachers to be among the psychological factors implicated in bulling while 12 psychological measures were also identified as effective for repressing bullying among in-school adolescents in Anambra state. Based on the findings, it was recommended that parents should teach their children to express their emotions in socially appropriate ways and regulate their emotions effectively.